Trust Requirements in E-Health System: A Conceptual Framework - Kamalrudin, M.; Winarsih, N.A.S.; Sidek, S. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Resulting from the development of new technology, conventional scientific practices have migrated into computer-based infrastructures, called e-science. Specifically, escience applied in health discipline is called e-health. It is an organized system that deals to diagnose and treat patients. Considering trust is an important role and fundamental for the provision of effective healthcare service, this paper discusses trust requirement in e-health. To highlight the importance of trust in e-health system, a conceptual framework of trust requirements in e-health system is developed. Drawn from literature search framed by STARLITE, a conceptual framework that addresses trust resulting from relationships of various actors based on two perspectives: sociotechnical and technical perspectives are presented. This framework suggests that e-health system must build a trust relationship between actors and understand trust based on sociotechnical and technical perspectives. Further, security and privacy that protect the confidentiality of patient’s data, especially m-health (mobile health) also need trust in resource sharing. It can be concluded that trust requirements in e-health depend on how the media transmits a social experience, patient-system relationship, and collaboration of software engineering and healthcare professionals. The implementation of trust requirements has the potential to produce well-engineered software in a healthcare organization, resulting in the use of software for effective diagnosis and treatment of patients.